Perlindungan Hukum Terhadap Pekerja Atas Alat Pelindung Diri - Fitri Hardianti Solicha; Asri Wijayanti (Wijayakusuma Law Review, 2020)
Abstract Every worker must get a guarantee for occupational safety and health while carrying out the work relationship. This research aimed to find out the form of legal protection for workers for their personal protection devices and legal remedies. This research was a normative juridical with statute approach. The first research result showed that every worker was guaranteed their right to occupational safety and health integrated with the company's management system. Employers were required to provide explanations and self-protective equipment to workers who were obliged to use them. There was a threat of criminal sanctions for violating entrepreneurs. The second research result showed a civil law effort. It can be done by workers if they do not get an explanation and personal protective equipment that can conduct bipartite deliberation or mediation and continue to the PHI for the harm caused. Criminal legal remedies can be undertaken by workers by reporting K3 violations to local labor inspector employees. It was concluded that the employer had the obligation to provide an explanation and self-protective equipment. The workers were entitled and obliged to use self-protective equipment. There were criminal sanctions for employers who violated but there were not criminal sanctions for workers who violate. The resulting recommendations were the sanctions for workers.Keywords: Legal Protection, Protection Tools, Workers. Occupational Health and SafetyÂ AbstrakSetiap pekerja harus mendapatkan jaminan atas keselamatan dan kesehatan kerja selama menjalankan hubungan kerja penelitian ini bertujuan untuk mengetahui bentuk perlindungan hukum terhadap pekerja atas alat perlindungan diri beserta upaya hukumnya. Penelitian ini adalah yuridis normatif dengan pendekatan statute approach hasil penelitian yang pertama adalah setiap pekerja dijamin haknya atas keselamatan dan kesehatan kerja yang terintegrasi dengan sistem manajemaan perusahaan. Pengusaha diwajibkan memberikan penjelasan dan APD terhadap pekerja ,pekerja berkewajiban menggunakannya. Ada ancaman sanksi pidana bagi pengusaha yang melanggar. Hasil penelitian yang kedua adalah upaya hukum keperdataan yang dapat dilakukan pekerja apabila tidak mendapatkan penjelasan dan alat pelindung diri dapat melakukan musyawarah bipartite atau mediasi dan berlanjut ke PHI untuk kerugian yang ditimbulkannya. Upaya hukum kepidanaan dapat dilakukan oleh pekerja dengan melaporkan pelanggaran K3 kepaada pegawai pengawas ketenagakerjaan setempat. Kesimpulannya pengusaha memiliki kewajiban memberikan penjelasan dan APD ,pekerja berhak dan berkewajiban menggunakan APD, ada sanksi pidana bagi pengusaha yang melanggar tetapi tidak sanksi pidana bagi pekerja yang melanggar. Rekomendasi yang dihasilkan adalah pemberian sanksi kepada pekerja.Kata Kunci : perlindungan hukum, alat perlindungan , pekerja. Keselamatan dan kesehatan kerja